Saved by the Boats: The Heroic Sea Evacuation of September 11 - Julie Gassman (United States Capstone Press, 2016)
September 11, 2001 was a black day in U.S. history. Amid the chaos, sea captains and crews raced by boat to the tragic Manhattan scene. Nearly 500,000 people on Manhattan Island were rescued that day in what would later be called the largest sea evacuation in history. In this rarely told story of heroism, we come to understand that in our darkest hours, people shine brightly as a beacon of hope.
Keywords: Circle Time